Assessment of cryopreserved sperm functions of Korean native brindled cattle (Chikso) from different region research centers of Korea - Lei Ma; Dae-Jin Jung; Eun-Ju Jung; Woo-Jin Lee; Ju-Mi Hwang; Jeong-Won Bae; Dae-Hyun Kim; Jun Koo Yi; Sang Moo Lee; Jae Jung Ha; Woo-Sung Kwon (The Korean Society of Animal Reproduction and Biotechnology, 2021)
Sperm cryopreservation is an important method of assisted reproductive techniques and storing genetic resources. It plays a vital role in genetic improvement, livestock industrial preservation of endangered species, and clinical practice. Consequently, the cryopreservation technique is well organized through various studies, especially on Korean native cattle (Hanwoo). However, the cryopreservation technique of Korean native brindled cattle, which is one of the native cattle species in Korea, is not well organized. Therefore, it is necessary to develop a Supplementary Table technique for the cryopreservation of Korean native brindled cattle. For this purpose, it is important to first evaluate the quality of the currently produced cryopreserved sperm of Korean native brindled cattle. In this study, we randomly selected 72 individual Korean native brindled cattle semen samples collected from 8 different region research centers and used them to evaluate sperm functions. We focused on the quality evaluation of cryopreserved Korean native brindled cattle semen following the measurement of motion kinematics, capacitation status, intracellular ATP level, sperm motility, and cell viability. Then, the values of each of the eight groups were derived from various sperm parameters of nine individual samples, including sperm motility, kinematics, cellular motility, and intracellular ATP levels, which were used to compare and evaluate sperm function. Overall, differences in various sperm parameters were observed between most of the research centers. Particularly, the deviations of motility and motion kinematics were high according to the sample. Therefore, we suggest that it is necessary to develop a standard method for the cryopreservation of Korean native brindled cattle semen. We also suggest the need for sperm quality evaluation of the cryopreserved semen of Korean native brindled cattle before using artificial insemination to attain a high fertility rate.